Soft (perceptual) metrology: dissemination of information-measuring technologies in the area “Measuring the impossible”. - Motalo, Vasyl; Chereshnevska, Anzhelika; Savitska, Yuliia (Видавництво Львівської політехніки, 2020)
The article focuses on the main problems of the development of the soft (perceptual) metrology as one of the new progressive areas of modern metrology that has appeared as a result of the dissemination of the information measuring technologies into the field of knowledge of non-physical phenomena and processes. An overview and analysis of well-known works on the topic of soft metrology are conducted. The areas of soft metrology research have been considered and analyzed, in particular, the investigation of the correlation between human, subjective responses to stimuli and physical, objective measurements. The question of the methodology of carrying out sensometrical measurements, that is, measurements of quantities characterizing the human sensations and responses to stimuli is considered. The main tasks of the research in the field of soft metrology for the implementation of its concept in practical applications, in particular in robotics have been established.
Keywords: Soft Metrology; Information Measuring Technologies; Human Senses; Stimuli; Sensors; Sensometrical Measurements; Robotics